2020
DOI: 10.14689/ejer.2020.86.7
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Leaders for Building Trust in the School Context

Abstract: The purpose of this study was to analyze the impact of spiritual leadership on organizational trust and examine the relationship between both concepts. Research Method: A multiple regression analysis was carried out using the data collected through spiritual leadership and organizational trust scales from 343 teachers. Findings: The result of the study revealed that the dimensions of spiritual leadership have varying relationships with organizational trust, which is significantly predicted by altruistic love, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(39 reference statements)
0
9
0
3
Order By: Relevance
“…According to Terzi, Gocen and Kaya (2020), the dimensions of SL have varying relationships with organizational trust, which is significantly predicted by altruistic love, hope/faith and OC. For Tabor, Madison, Marler and Kellermanns (2020), OC is boosted by SL but decreased by work–family conflict.…”
Section: Discussion Of Results From the Analysis Of The Relationship ...mentioning
confidence: 99%
“…According to Terzi, Gocen and Kaya (2020), the dimensions of SL have varying relationships with organizational trust, which is significantly predicted by altruistic love, hope/faith and OC. For Tabor, Madison, Marler and Kellermanns (2020), OC is boosted by SL but decreased by work–family conflict.…”
Section: Discussion Of Results From the Analysis Of The Relationship ...mentioning
confidence: 99%
“…Whilst spirituality (e.g. SI) necessitates trust to exist (Terzi et al , 2020) for sustainability (Sarmawa et al , 2020). Furthermore, EI can build trust among organizational members to tackle crisis situations and generate an efficient working environment (Porter, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Past research found that leaders' spirituality predicted employee trust (Terzi et al, 2020), whilst trust is a principal element of sustainable organizations (Jabło nski and Ko_ zuch, 2019).…”
Section: Trustmentioning
confidence: 99%
“…In recent years, researchers have begun to investigate the importance of spirituality in schools in recent years (Aksakal & Kahveci;2021;Cook & Babyak, 2019;Paul et. al., 2020;Terzi et. al.…”
Section: Introductionmentioning
confidence: 99%